Host species is linked to pathogen genotype for the amphibian chytrid fungus (Batrachochytrium dendrobatidis) - Allison Q. Byrne; Anthony W. Waddle; Veronica Saenz; Michel Ohmer; Jef R. Jaeger; Corinne L. Richards-Zawacki; Jamie Voyles; Erica Bree Rosenblum (PLoS ONE, 2022)
Host-pathogen specificity can arise from certain selective environments mediated by both the host and pathogen. Therefore, understanding the degree to which host species identity is correlated with pathogen genotype can help reveal historical host-pathogen dynamics. One animal disease of particular concern is chytridiomycosis, typically caused by the global panzootic lineage of the amphibian chytrid fungus (Batrachochytrium dendrobatidis, Bd), termed Bd-GPL. This pathogen lineage has caused devastating declines in amphibian communities around the world. However, the site of origin for the common ancestor of modern Bd-GPL and the fine-scale transmission dynamics of this lineage have remained a mystery. This is especially the case in North America where Bd-GPL is widespread, but disease outbreaks occur sporadically. Herein, we use Bd genetic data collected throughout the United States from amphibian skin swabs and cultured isolate samples to investigate Bd genetic patterns. We highlight two case studies in Pennsylvania and Nevada where Bd-GPL genotypes are strongly correlated with host species identity. Specifically, in some localities bullfrogs (Rana catesbeiana) are infected with Bd-GPL lineages that are distinct from those infecting other sympatric amphibian species. Overall, we reveal a previously unknown association of Bd genotype with host species and identify the eastern United States as a Bd diversity hotspot and potential site of origin for Bd-GPL.